A Systematic Review of Security Challenges in Distributed Cloud Computing Based on the CIA Triad: Tinjauan Sistematis Tantangan Keamanan pada Cloud Computing Terdistribusi Berbasis CIA Triad - Dian Puspita Sari Andri; Rahmaniar Rahmaniar (Program Studi Teknologi Rekayasa Komputer dan Jaringan, Politeknik Wahdah Islamiyah Makassar, 2026)
This study aims to identify and classify security challenges in distributed cloud computing systems based on the aspects of Confidentiality, Integrity, and Availability (CIA). The research employs a Systematic Literature Review with a narrative analysis of articles published between 2021 and 2026, resulting in 15 selected studies through a structured inclusion and exclusion process. The findings indicate that confidentiality challenges include data breaches, unauthorized access, and data leakage, primarily driven by multi-tenancy and weak access control. In terms of integrity, the main risks involve data manipulation, misconfiguration, and limitations in verification mechanisms within distributed systems. Meanwhile, availability is threatened by Distributed Denial of Service (DDoS) attacks, node failures, and architectural complexity. Various security methods have been proposed, including encryption, access control, intrusion detection systems, as well as advanced approaches such as risk assessment, Trusted Execution Environments, Information Flow Tracking, and Zero Trust Architecture. This study highlights that cloud security is complex and multidimensional, requiring an integrated multi-layered security approach. The CIA model remains a fundamental foundation, supported by adaptive solutions to address the evolving dynamics of distributed systems.